Handel, Messiah - Burrows, Donald 1945- (Cambridge University Press, 1991)
This new guide to Handel's most celebrated work traces the course of Messiah from Handel's initial musical response to the libretto, through the oratorio's turbulent first years to its eventual popularity with the Foundling Hospital performances. Different chapters consider the varying reception the work received in Dublin and London, the uneasy relationship between the composer and his librettist Charles Jennens and the many changes Messiah underwent through the varying needs and capacities of Handel's performers. As well as tracing the history of the work's development, the book addresses musical and technical issues such as Messiah's place in the oratorio genre, Handel's treatment of structural design, tonal relationships and English word-setting. An edited libretto elucidates the variants between the text that Handel set and the texts of the early printed word-books. Donald Burrows brings many new insights to this fascinating account of one of the favourite works of the concert hall
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Handel, George Frideric / 1685-1759 / Messiah; Händel, Georg Friedrich -- 1685-1759 -- Messiah